Safety Inspections of Public Transport Modes in Accordance with Law No. 22 of 2009 Concerning Traffic and Road Transportation at the Service Unit of Type A Terminal in Bawen - Ayattullah Khumaini Abdul Rozak; Irfan Rizky Hutomo; Lailasari Ekaningsih; Ridho Sa’dillah Ahmad; Mohammad Tohari (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2024)
Data collected from various sources indicates that traffic accidents remain a significant issue. The Indonesian National Police's Traffic Corps (Korlantas Polri) claims that the number of accidents across Indonesia has decreased over the past four years. This statement was made by AKBP Hendra Wahyudi, the Head of the Traffic Sub-Directorate, Ditgakkum. According to him, in 2019, the number of accidents reached 116,411 cases, which was higher than the 100,028 cases reported in 2020. In 2021, the number further decreased to 103,645 incidents, and by 2022, only 55,777 accidents had occurred. "The number of fatalities in 2019 reached 25,671, while in 2020 it dropped to 23,529. However, the number of deaths rose again in 2021 to 25,266, and by May 2022, there were already 11,183 fatalities," he emphasized. The primary cause of accidents is generally attributed to driver error. According to the most recent data from 2022, 15,885 accidents were caused by driver inattention, 15,315 by failure to maintain a safe following distance, and the remainder by negligence during turns. The distribution of accident locations is quite varied.